Tanggung Jawab Pemegang Protokol Notaris Terhadap Akta Yang Batal Demi Hukum - Oktavia, Dewi (Recital Review, 2021)
Abstract This study aims to, 1) find out and analyze the form of responsibility of the recipient of the Notary protocol to the deed declared null and void by law. 2) Legal protection for Notary protocol holders against deeds that are null and void by law. The formulation of the study’s masalash are, 1) What is the form of the recipient of the Notary protocol’s answer to the deed that was declared null and void. 2) Legal protection for Notary protocol holders against deeds that are null and void by law. This research is a normative legal research, which is conducted by examining legal materials, such as research on legal principles, as well as positive law in Indonesia. This study uses 3 (three) methods of approach in legal research, namely conceptual suppressors, legislative approaches and case approaches. The results of this study are the Notary who has accepted the protocol is responsible for maintaining the notary protocol that is transferred to him. and also authorized to issue Grosse Deed, Copy of Deed, or Deed Quotation, regarding the material on the deed made beforehand not the responsibility of Notary recipient of the protocol. Legal protection for the recipient of the protocol does not provide legal protection because in the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public has not been regulated. Â Keywords: Responsibility, Notary Protocol, Deed.